The Auditory-Visual Speech Benefit on Working Memory in Older Adults with Hearing Impairment - Frtusova, Jana B.; Phillips, Natalie A. (Frontiers in Psychology, 2016)
This study examined the effect of auditory-visual (AV) speech stimuli on working memory in hearing impaired participants (HIP) in comparison to age- and education-matched normal elderly controls (NEC). Participants completed a working memory n-back task (0- to 2-back) in which sequences of digits were presented in visual-only (i.e., speech-reading), auditory-only (A-only), and AV conditions. Auditory event-related potentials (ERP) were collected to assess the relationship between perceptual and working memory processing. The behavioural results showed that both groups were faster in the AV condition in comparison to the unisensory conditions. The ERP data showed perceptual facilitation in the AV condition, in the form of reduced amplitudes and latencies of the auditory N1 and/or P1 components, in the HIP group. Furthermore, a working memory ERP component, the P3, peaked earlier for both groups in the AV condition compared to the A-only condition. In general, the HIP group showed a more robust AV benefit; however, the NECs showed a dose-response relationship between perceptual facilitation and working memory improvement, especially for facilitation of processing speed. Two measures, reaction time and P3 amplitude, suggested that the presence of visual speech cues may have helped the HIP to counteract the demanding auditory processing, to the level that no group differences were evident during the AV modality despite lower performance during the A-only condition. Overall, this study provides support for the theory of an integrated perceptual-cognitive system. The practical significance of these findings is also discussed.